Strengthening Trainers' Transfer Knowledge: An Intervention Study - Alisha Koch; Susanne Wisshak (International Journal of Training and Development, 2025)
Although continuous vocational education and training (CVET) trainers are relevant stakeholders who can initiate and support transfer, they have received little attention in the context of transfer research, especially with respect to their transfer knowledge. In this study, we investigated the extent to which the transfer knowledge of CVET trainers can be increased through an intervention. Based on our conceptualization of transfer knowledge, which is a three-dimensional construct that includes knowledge about learner characteristics, training design and the work environment, we implemented a 5-week digital training programme (intervention) for CVET trainers. We employed a nonrandomized pretest‒posttest design to investigate N 0.167em=0.167em81 trainers and examined the effects of the training programme on trainers' transfer knowledge. While 47 trainers participated in the training programme (experimental group), 34 trainers were included in the control group and received no intervention. As hypothesized, we found a significant interaction effect on the development of trainers' transfer knowledge ( ηp20.167em=0.167em0.386). Furthermore, we found significant interaction effects pertaining to all three dimensions of transfer knowledge: learner characteristics ( ηp20.167em=0.167em0.196), training design ( ηp20.167em=0.167em0.246) and the work environment ( ηp20.167em=0.167em0.279). Thus, the experimental group exhibited a significant increase in transfer knowledge. No such development was observed among the control group during the intervention period. Hence, the findings of this research provide initial indications that transfer knowledge is learnable and can be increased through an intervention. Further studies are necessary to evaluate whether trainers also transfer training content to their own training courses.
Keywords: 650; teaching in continuing vocational education and training (CVET); trainer; training programme; train-the-trainer programme; transfer of training; transfer knowledge